Chemical constituents and biological activities of Mitrella kentii (Blume) miq. leaf oil - Juriyati Jalil; Sakina Saadawi; Ibrahim Jantan; Malina Jasamai (Penerbit Universiti Kebangsaan Malaysia, 2021)
Chemical constituents and biological activities of the Mitrella kentii leaf oil were investigated in this study. Gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS) were used to determine the chemical constituents of the oil. The oil was evaluated for its ability to inhibit prostaglandin E2 (PGE2 ) and thromboxane B2 (TXB2 ) productions in human whole blood using a radioimmunoassay technique. Its inhibitory effect on plateletactivating factor (PAF) receptor binding with rabbit platelets using 3 H-PAF as a ligand and its free radical scavenging effect on DPPH were also investigated. Caryophyllene oxide (33.8%w/w), E,Z-farnesol (6.9%), benzyl benzoate (6.5%w/w) and viridiflorol (6.5%w/w) were among the major components of the oil. Even though weak inhibitory activities were observed in both PGE2 and TXB2 assays, significant results were obtained in both PAF receptor binding inhibition and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging effect with IC50 value of 6.6 µg/mL and 155.6 µg/mL respectively. These promising activities warrant the development of the oil as an anti-inflammatory agent.